Movimento expandido: Confluência entre a dança e o teatro na criação do bailarino - Gabriela Cordova Christofaro (2008)
This dissertation investigates the confluence of dance and theater within the composition of the dancer, conceived herein as a participant of the creation and of the scene.The research, based upon a theoretical study and statements given by some of Belo Horizontes dancers who participated in creative processes involving the interfaces of theater and dance, is interested in the way the body is conducted when serving the choreographic composition.We contemplated the concept of movement under the perspective of Rudolf Von Laban, and the concept of physical action according to Constantin Stanislavski, Gerzy Grotowski and Luis Otávio Burnier. Starting from these, we established referential bases for the proposed reflection: body, space and time, under physical as well as situational and relational aspects.The investigation of the dancers work was developed through the identification, within their creative processes, of the references established, the characteristics presented by these references, and the way they were used.We conclude our research with the chapter Expanded Movement, in which we propose an articulation between the concepts of movement and physical action, reelaborating issues raised in the dancers statements, and providing our considerations on the artistic mobility potentials of the body.